Relaxation-Time Modeling for NQS Phenomena Characterization in High-Frequency Diodes. - García Luque, Aarón; Martín-Guerrero, Teresa María; Mata-Contreras, Francisco Javier (My University, 2023)
AbstractÐA characterization methodology for nonquasi-static (NQS) phenomena in high frequency electron devices is carried out in this work. The proposed nonlinear diode model includes a S-parameters-based procedure for the estimation of the parasitic network, and the direct extraction of the nonlinear intrinsic state functions from single-tone measurements. This NQS proposal, based on a first-order electric charge source, was validated for some commercial diodes improving the prior QS model when frequency rises. A voltage-discretization analysis and some small signal (0.7-20 GHz) and waveforms (f0 = 2 and 8 GHz) tests, prove the successful performance of these circuits and their frequency extrapolation possibilities versus foundry models.
Keywords: Procesos irreversibles; Diodos; Analizadores de redes eléctricas; Nonquasi-Static Phenomena; Varactor; Schottky Diode; Nonlinear Network Vector Analyzer